Vocational Training as an Integration Opportunity for Struggling Young Adults? A Swiss Case Study. - Maël Dif-Pradalier; Emilie Rosenstein; Jean-Michel Bonvin (Social Work & Society, 2012)
The aim of this paper is to assess a Swiss s school-to-work transition programme against the capability approach. Our objective is to examine to what extent it enhances youngsters' capabilities by providing resources and conversion factors allowing them to project themselves in the future and plan their own life in a way they have reason to value. The impact of the programme is assessed with regard to its beneficiaries' capability for voice, for education and for work. The paper answers the three following research questions: -    What is the impact of the individualised approach promoted by the programme on the recipients' capability for voice? -    How does the programme integrate a life course perspective and to what extent does it take into account the beneficiaries' capacity to aspire? -    What is the impact of the programme on the supply and demand sides of the labour market?